2021
DOI: 10.7554/elife.62503
|View full text |Cite
|
Sign up to set email alerts
|

Starvation-induced regulation of carbohydrate transport at the blood–brain barrier is TGF-β-signaling dependent

Abstract: During hunger or malnutrition, animals prioritize alimentation of the brain over other organs to ensure its function and, thus, their survival. This protection, also-called brain sparing, is described from Drosophila to humans. However, little is known about the molecular mechanisms adapting carbohydrate transport. Here, we used Drosophila genetics to unravel the mechanisms operating at the blood–brain barrier (BBB) under nutrient restriction. During starvation, expression of the carbohydrate transporter Tret1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 96 publications
0
17
0
Order By: Relevance
“…2C and S6C). The SG2-biased genes Tret1 ( 69, 70 ) and svp ( 71 ) are established markers for perineurial glia, which is the peripheral layer of surface glia in fly ( 69, 71 ), leading us to conclude that SG2 cells, which exclusively express cf Jhe, correspond to perineural glia. Genes expressed by SG1 and SG2 shared similar functional terms indicative of the BBB, including “InR/TOR signal pathway”, which is required for proliferation of surface glia ( 72, 73 ) (Table S5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C and S6C). The SG2-biased genes Tret1 ( 69, 70 ) and svp ( 71 ) are established markers for perineurial glia, which is the peripheral layer of surface glia in fly ( 69, 71 ), leading us to conclude that SG2 cells, which exclusively express cf Jhe, correspond to perineural glia. Genes expressed by SG1 and SG2 shared similar functional terms indicative of the BBB, including “InR/TOR signal pathway”, which is required for proliferation of surface glia ( 72, 73 ) (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…Each Major (or Minor) were labeled as a "individual" with 8 "bodyparts" (3 at head, 2 at thorax, 3 at abdomen) and cotton ball "food" was labeled as a static "object". 70 Frames for which food or ant prediction likelihood was below 0.8 were removed. Foraging performance was evaluated based on mean number of workers present in foraging arena per night (normalized by number of workers per replicate), and "times approaching food" (number of times an ant comes within 20% of total area radius to food after being > 25% of arena radius from food).…”
Section: Ant Foraging Data Analysismentioning
confidence: 99%
“…Under full starvation, perineurial glia increases the levels of the carbohydrate transporter Tret1-1. 57 However, under a sucrose-only diet, Tret1-1 levels are similar to in a normal diet, suggesting that BBB carbohydrate transport is sensitive to larval glycemia. 57 Indeed, using a FRET-based glucose sensor, Hertenstein et al 57 showed that under starvation, glucose uptake in the BBB is increased compared to fed conditions, and this increase depends on the upregulation of Tret1-1.…”
Section: The Drosophila Blood-brain Barrier Acts A...mentioning
confidence: 94%
“… 57 However, under a sucrose-only diet, Tret1-1 levels are similar to in a normal diet, suggesting that BBB carbohydrate transport is sensitive to larval glycemia. 57 Indeed, using a FRET-based glucose sensor, Hertenstein et al 57 showed that under starvation, glucose uptake in the BBB is increased compared to fed conditions, and this increase depends on the upregulation of Tret1-1. Thus, the larval BBB may promote neurogenesis, and therefore brain sparing, by enhancing carbohydrate uptake from the hemolymph in a starvation condition, while other tissues stop developing ( Figure 2C ).…”
Section: The Drosophila Blood-brain Barrier Acts A...mentioning
confidence: 94%
“…Both aging and starvation led to a decrease in the amount of the metabolic enzyme glycogen phosphorylase in the BBB [300]. In Drosophila, starvation leads to an increase in expression of the carbohydrate transporter Tret1-1 to maintain a prioritized nutrient supply of the brain in times of insufficiency [301]. 9.2.…”
Section: Factors Altering Structure and Functionmentioning
confidence: 99%